Cation exchange membranes by radiation-induced graft copolymerization of styrene onto PFA copolymer films. I. preparation and characterization of the graft copolymer - Mohamed Mahmoud, Nasef (John Wiley & Sons, 1999)
PFA-g-polystyrene graft copolymers were prepared by simultaneous radiation- induced graft copolymerization of styrene onto poly(tetrafluoroethylene-co-perfluorovinyl ether) (PFA) films. The effects of grafting conditions such as monomer concentration, dose, and dose rate were investigated. Three solvents, i.e., methanol, benzene, and dichloromethane, were used as diluents in this grafting system. Of the three solvents employed, dichloromethane was found to greatly enhance the grafting process, and the degree of grafting increased with the increase of monomer concentration until it reached its highest value at a styrene concentration of 60 (vol %). The dependence of the initial rate of grafting on the monomer concentration was found to be of the order of 1.2. The degree of grafting was found to increase with the increase in irradiation dose, while it considerably decreased with the increase in dose rate. The formation of graft copolymers was confirmed by FTIR analysis. The structural investigation by X-ray diffraction (XRD) shows that the degree of crystallinity content of such graft copolymers decreases with the increase in grafting, and consequently, the mechanical properties of the graft copolymers were influenced to some extent. Both tensile strength and elongation percent decreased with the increase in the degree of grafting.